Compressive strength and microstructural analysis of fly ash/palm oil fuel ash based geopolymer mortar - Ranjbar, Navid; Mehrali, Mehdi; Behnia, Arash; Alengaram, U. Johnson; Jumaat, Mohd Zamin (Materials in engineering, 2014)
•Results show POFA is adaptable as replacement in FA based geopolymer mortar.•The increase in POFA/FA ratio delay of the compressive development of geopolymer.•The density of POFA based geoploymer is lower than FA based geopolymer mortar. This paper presents the effects and adaptability of palm oil fuel ash (POFA) as a replacement material in fly ash (FA) based geopolymer mortar from the aspect of microstructural and compressive strength. The geopolymers developed were synthesized with a combination of sodium hydroxide and sodium silicate as activator and POFA and FA as high silica–alumina resources. The development of compressive strength of POFA/FA based geopolymers was investigated using X-ray florescence (XRF), X-ray diffraction (XRD), Fourier transform infrared (FTIR), and field emission scanning electron microscopy (FESEM). It was observed that the particle shapes and surface area of POFA and FA as well as chemical composition affects the density and compressive strength of the mortars. The increment in the percentages of POFA increased the silica/alumina (SiO2/Al2O3) ratio and that resulted in reduction of the early compressive strength of the geopolymer and delayed the geopolymerization process.